'Invisible in a visible role': a photovoice study exploring the struggles of new resident assistants. Issue 5 (28th May 2021) - Cheng, Michelle W.T.; Chan, Cecilia K.Y.
ABSTRACT: Past studies revealed that Resident Assistants' (RAs) behavioural patterns are related to experiences and life outcomes of student residents. In this paper, the researchers aimed to investigate the struggles that new RAs encounter in university residential halls in Hong Kong, and to provide practical recommendations based on the findings. Photovoice was adopted to facilitate the participatory approach of the study; and six new RAs were recruited from different residential halls in a university for one semester to co-construct reliable knowledge. Four domains of struggles were identified in the study; difficulties to blend in, levels of involvement, workloads and performance, and role ambiguity. Further research is needed in different contexts to provide more insights to refine policies and approaches for better RAs' residential environment, as it is believed that by improving their residential experiences, it can further enhance students' residential experiences and foster positive residence life outcomes.